2002
DOI: 10.1021/bi026454l
|View full text |Cite
|
Sign up to set email alerts
|

E. coli Expression of TIMP-4 and Comparative Kinetic Studies with TIMP-1 and TIMP-2:  Insights into the Interactions of TIMPs and Matrix Metalloproteinase 2 (Gelatinase A)

Abstract: The inhibitory properties of TIMP-4 for matrix metalloproteinases (MMPs) were compared to those of TIMP-1 and TIMP-2. Full-length human TIMP-4 was expressed in E. coli, folded from inclusion bodies, and the active component was purified by MMP-1 affinity chromatography. Progress curve analysis of MMP inhibition by TIMP-4 indicated that association rate constants (k(on)) and inhibition constants (K(i)) were similar to those for other TIMPs ( approximately 10(5) M(-)(1) s(-)(1) and 10(-)(9)-10(-)(12) M, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 61 publications
8
51
0
Order By: Relevance
“…TIMP-4 exhibited a comparable lower affinity for both MT3-MMP cat and MT1-MMP cat (K i ϭ 0.3 nM) ( Table I). The affinity of TIMP-4 for MT1-MMP cat is in good agreement to that previously reported by Troeberg et al (25). TIMP-1 interaction with MT1-MMP cat has been shown to be practically negligible (22,55) and, at concentrations up to 9 nM, showed no inhibition of MT3-MMP cat (data not shown).…”
Section: Timp-3 But Not Timp-4 Supports Pro-mmp-2 Activation By Mt3-msupporting
confidence: 92%
See 2 more Smart Citations
“…TIMP-4 exhibited a comparable lower affinity for both MT3-MMP cat and MT1-MMP cat (K i ϭ 0.3 nM) ( Table I). The affinity of TIMP-4 for MT1-MMP cat is in good agreement to that previously reported by Troeberg et al (25). TIMP-1 interaction with MT1-MMP cat has been shown to be practically negligible (22,55) and, at concentrations up to 9 nM, showed no inhibition of MT3-MMP cat (data not shown).…”
Section: Timp-3 But Not Timp-4 Supports Pro-mmp-2 Activation By Mt3-msupporting
confidence: 92%
“…Our data also showed that TIMP-4 is a potent inhibitor of MT3-MMP as it is of MT1-MMP (22,25,71) and MT2-MMP (23). However, despite its ability to bind pro-MMP-2 (24), albeit with lower affinity than TIMP-2 (25), TIMP-4 was unable to support pro-MMP-2 activation by MT3-(shown here), MT1-(22, 26), or MT2-MMP (23).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Proteins and Antibodies-Recombinant human pro-MMP-2 and TIMP-2 were expressed in HEK-293 cells using the mammalian expression vector pCEP4 (Invitrogen) (33). Pro-MMP-2 was purified using gelatin-Sepharose affinity chromatography and gel filtration with S-200 (Amersham Biosciences) as described previously (34).…”
Section: Methodsmentioning
confidence: 99%
“…The activity of MMPs can be regulated by endogenous inhibitors, which include the TIMPs, 21 a 2 -macroglobulin 22 and the membrane-anchored glycoprotein RECK (for ''reversioninducing cysteine-rich protein with kazal motifs''). 23 There are 4 vertebrate TIMPs.…”
Section: Endogenous Inhibitors Of Metalloproteinasesmentioning
confidence: 99%